What's in a name? A call to reframe non-communicable diseases - Allen, L; Feigl, A (Lancet, 2017)
The global health community does not spend much time on branding, which perhaps explains why existing classifications for the three largest groups of diseases are both outdated and counterproductive. The first Global Burden of Disease study1 described infectious diseases, non-communicable diseases (NCDs), and injuries. This grouping reflected a predominantly infectious disease burden in low-income and middle-income countries, which has since tilted towards NCDs. A name that is a longwinded non-definition, and that only tells us what this group of diseases is not, is not befitting of a group of diseases that now constitute the world's largest killer.